Cryo-capacitation changes during cryopreservation of swamp buffalo spermatozoa - TALUKDAR, D J; AHMED, K; DEKA, B C; SINHA, S; DEORI, S; DAS, G C (The Indian Journal of Animal Sciences, 2016)
Cryopreservation of sperm cells induces cryo-capacitation like changes. These changes are associated with reduced survival of sperm cells in the female reproductive tract that ultimately associate with poor fertility. The present study was designed with the objective to investigate the cryo-capacitation changes in relation to acrosomal status, transaminases activities, sperm membrane protein and cholesterol content in swamp buffalo spermatozoa. Results revealed that the total mean incidences of acrosome reacted spermatozoa and the mean activity of ALT and AST were significantly higher after equilibration and freezing. The mean level of sperm membrane protein and cholesterol was significantly lower after equilibration and freezing. It may be concluded from the present study that cryopreservation induces capacitation-like changes in swamp buffalo spermatozoa.